Metodología SLP para la distribución en planta de empresas productoras de Guadua Laminada Encolada (G.L.G) - Torres, Kelly Jhoana; Florez Peña, Laura Sofía; Sánchez, Carlos William; Castañeda Peñaranda, Mauricio (Ingeniería, 2020)
Context: The guadua Angustifolia Kunth is a plant derived from bamboo, it is a woody grass that has been identified as vegetable steel, thanks to its properties of flexibility, hardness and elasticity that allows its use at an industrial level as an input for manufacturing planks which are made of laminated guadua (Guadua laminated with glue) that can be used to manufacture beams and other structural elements required by architecture. Method: In this case, the plant distribution design document was used using the SLP (systematic design planning) methodology, taking the company Guadua Viga as a case of study, where the company processes are characterized and analyzed, the initial requirements were defined and the design of the distribution in the plant was carried out, finally the proposals were evaluated in terms of costs Results: 3 distribution proposals were made according to the needs of the company and the production process of laminated guadua boards and the alternatives were evaluated in terms of efficiencies. Conclusion: The alternative that was proposed requires 4148 m2, has an efficiency of 89% regarding the flow of materials, 62% efficiency regarding the flow of materials and adjacency.